1999
DOI: 10.1046/j.1460-2695.1999.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

There is no infinite fatigue life in metallic materials

Abstract: Generally, the shape of the S–N curve beyond 107 cycles is unknown except in some statistical approaches, and this is also true for the fatigue limit. In the case of a statistical approach, the standard deviation applied to the average fatigue limit is certainly not the best way to reduce the risk of rupture in fatigue. Only the exploration of the life range between 106 and 1010 cycles will create a safer basis for modelling. Today, some piezoelectric fatigue machines are very reliable, capable of producing 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
194
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 453 publications
(237 citation statements)
references
References 8 publications
5
194
0
3
Order By: Relevance
“…Inclusion can be active crack initiation sites, especially if the load ratio is high. The porosities can initiate a crack in competition with inclusions, especially when the load ratio is low, particularly in pull-push (Bathias, 1999). Another explanation of fatigue crack initiation in gigacycle regime is by stress concentration between two or more grains where a long grain boundary is located perpendicular to the pull stress and therefore it works as an internal notch.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion can be active crack initiation sites, especially if the load ratio is high. The porosities can initiate a crack in competition with inclusions, especially when the load ratio is low, particularly in pull-push (Bathias, 1999). Another explanation of fatigue crack initiation in gigacycle regime is by stress concentration between two or more grains where a long grain boundary is located perpendicular to the pull stress and therefore it works as an internal notch.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increasingly more attention has been given to material behaviour in the very high cycle regime from an experimental point of view. The general belief that steel experiences no alteration in its properties after reaching its fatigue limit at 10 7 cycles has been invalidated [21], [22], [23]. In this context, this paper provides a tool for rapid automatized time-advance that allows taking numerical simulations beyond the limit of 10 7 cycles in reasonable computational time.…”
Section: Introductionmentioning
confidence: 99%
“…The fatigue limit, which is often implemented as an important design parameter, cannot be used for metals subjected to low cyclic stresses, since different crack initiation and growth mechanisms become active below the threshold stress intensity factor range ΔK th , and failure can still occur after a large amount of cycles. 6 In the very high cycle fatigue regime, it has been found that the location of crack initiation tends to shift from the surface towards the subsurface and interior of the material. 3,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20] This shift is coupled with a knee or sudden drop in the S-N curve around 10 7 -10 8 cycles, which means that the fatigue strength becomes much lower at these long lifetimes.…”
Section: Introductionmentioning
confidence: 99%